The Dynamic Implications of Debt Relief for Low-Income Countries - Bulir, Ales (IMF Working Papers; Working Paper ;, 2011)
The effects of debt relief on incentives to accumulate debt, consume, and invest are an important concern for donors and recipients. Using a dynamic stochastic general equilibrium model of a small open economy with a minimum consumption requirement and an endogenous relief probability, we show that excessive debt accumulation is consistent with an anticipation of a future debt relief. Simulations of the calibrated model using 1982-2006 Ugandan data suggest that debt-relief episodes are likely to have only a temporary impact on the level of debt in low-income countries, while being associated with more consumption and less invesment. The long-run debt-to-GDP ratio is estimated to be about twice as high with debt relief than without it.